EVALUASI HASIL AKREDITASI LEMBAGA PAUD SE-KOTA DEPOK - Oktaria, Renti; Hamid, Lukman; Yuningsih, Yuningsih; Suparti, Suparti (Journal of Early Childhood Education (JECE), 2019)
The objectives to be achieved in this study are to analyze (1) descriptive results of accreditation throughout Depok's early childhood education centers in 2018; (2) the results of the distribution of accreditation throughout Depok's early childhood education centers in 11 districts; (3) the results of accreditation based on the length of the school's establishment, land area, and accreditation experience in each kindergarten program. This study uses a mix method research approach with critical analysis methods and library methods, so as to present quantitative data simply and describe it in qualitative data. The findings are as follows: (1) The number of accredited institutions is still dominated by early childhood education centers with TK programs, namely 97 institutions out of 186 institutions that participate in accreditation or as much as 52% of the total early childhood education centers that participate in accreditation; (2) There is an inequality in the number of accredited institutions in 11 districts in Depok; and (3) High and low accreditation scores do not always relate to the length of standing, land area and experience of institutions in implementing accreditation.